An algebra problem by A Former Brilliant Member

Algebra Level 2

The equation whose roots are the reciprocals of the roots of 2 x 2 3 x 5 = 0 2x^2-3x-5=0 is:

5 x 2 + 3 x 2 = 0 5x^2+3x-2=0 3 x 2 5 x 2 = 0 3x^2-5x-2=0 2 x 2 5 x 3 = 0 2x^2-5x-3=0 5 x 2 2 x 3 = 0 5x^2-2x-3=0

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Richard Costen
May 13, 2017

In quadratic eqn. a x 2 + b x + c = 0 ax^2+bx +c=0 , the product of the roots is c a \frac{c}{a} . In this case the product is 5 2 -\frac52 . The product of the reciprocals of the roots will be a c = 2 5 \frac{a}{c}=-\frac25 . Only the third eqn. satisfies this. Note that if the sum of the roots is m + n = b a m+n=-\frac{b}{a} , then the sum of the reciprocal roots will be 1 m + 1 n = m + n m n = b a c a = b c \frac{1}{m}+\frac{1}{n}=\frac{m+n}{mn}=\frac{-\frac{b}{a}}{\frac{c}{a}}=-\frac{b}{c} . In this case it would be 3 5 -\frac35 , which matches the b a -\frac{b}{a} in the third eqn. One can find the equation directly by using x 2 + b c x + a c = 0 x^2+\frac{b}{c}x+\frac{a}{c}=0 . Multiply by c c to simplify to: c x 2 + b x + a = 0 cx^2+bx+a=0 or 5 x 2 3 x + 2 = 0 -5x^2-3x+2=0 or 5 x 2 + 3 x 2 = 0 \boxed{5x^2+3x-2=0}

Denton Young
May 15, 2017

The roots of the original equation are 1 -1 and 5 / 2 5/2

The reciprocals of these are 1 -1 and 2 / 5 2/5 , so your equation is ( x + 1 ) ( 5 x 2 ) = 0 (x + 1)(5x-2) = 0

Multiplying out, you get 5 x 2 + 3 x 2 = 0 5x^2 + 3x - 2 = 0

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...